Prevalence of HPV in a Peruvian Healthcare Network: A Descriptive Cross-Sectional Study - Jhajaira M. Araujo MSc; Maria Ramon-Cotrina Br; Rosa Quispe-Martinez MD; Mayra Rios-Rios Br; Maribel Quispe-Gonzaga Br; Carlos O. Saldaña-Reyes Br; Paula Medina PhD; Melanie Cornejo PhD; Joseph A. Pinto MSc; Richard Dyer MD (Cancer Control)
Introduction Human papillomavirus (HPV) infection is a common sexually transmitted infection often associated with cancer development. This study aimed to estimate the prevalence of HPV in women receiving care at the AUNA healthcare network in Peru. Methods We conducted an observational, descriptive, cross-sectional, retrospective study. A de-identified database of HPV-positive women who underwent the BD Onclarity™ HPV Assay between December 2018 and December 2021 at Auna clinics was analyzed. The database contained information regarding age, city, and HPV type. High-risk HPV types were analyzed individually (16, 18, 31, 45, 51, 52) and pooled [P1 (33, 58), P2 (56,59,66), and P3 (35,39,68)]. The study was approved by an independent research ethics committee in Peru. Results Of 68,714 women included in the study, the HPV prevalence was 14.21% (N = 9765, 95%CI:13.95%–14.47%). The highest prevalence was detected in Piura (16.85%, 95%CI:15.40%–18.38%), where HPV-51, HPV-52, HPV-P1, HPV-P2, and HPV-P3 were most common compared to other Peruvian cities included in the study. In Arequipa, the prevalence was the lowest (13.58%, 95%CI:12.38%–14.85%), but the percentage prevalence of HPV-16 was the highest compared to other cities. The prevalence of multiple HPV infections was 2.88% (N = 1981, 95%CI:2.76%–3.01%), with most of them co-presenting two types of HPV (N = 1522). The most frequent co-occurrences were P2 and P3, P2 and 52, and P2 and 16. Among HPV-positive women, the mean age was 41.31 years (±9.48) and 25.29% were in the 31–35 years group. HPV-P2 was the most frequent in all age groups except in the 65–72 years group, where HPV-P3 was the most common. Conclusion HPV prevalence was shown to be highest in Piura, with the most prevalent types being HPV-16, HPV-52, and HPV-P2 (HPV-56, -59, -66). HPV infection was found to be more frequent among women in the 31–35 years age group.